Forecasting climate-driven changes in the geographical range of the European anchovy (Engraulis encrasicolus). (15th February 2017) - Raybaud, Virginie; Bacha, Mahmoud; Amara, Rachid; Beaugrand, Grégory
Abstract : Anthropogenic climate change is already affecting marine ecosystems and the responses of living-resources to warming waters are various, ranging from the modifications in the abundance of key species to phenologic and biogeographic shifts. Here, we used a recently developed Ecological Niche Model (ENM) to evaluate the potential effects of global climate change on the future geographical distribution of the European anchovy. We first modelled the ecological niche ( sensu Hutchinson) of the fish and projected its future spatial range using new IPCC representative concentration pathways (RCPs) scenarios and five of the latest generation of ocean-atmosphere global circulation models. We chose this multi-model and multi-scenario approach to evaluate the range of possible trajectories until the end of the century. Our projections indicate that substantial poleward shifts in the probability of anchovy occurrence are very likely and highlight areas where European anchovy fisheries are forecasted to change most. Whatever the warming scenario, our results project a reduction in the probability of occurrence in all the regions located under 48°N and an increase in more northern areas. However, increases or decreases in the probability of occurrence are greater under the "business-as-usual" scenario RCP8.5 than under the low-emission scenario RCP2.6.